Age-related changes in processing speed modulate context use during idiomatic ambiguity resolution. Issue 6 (2nd November 2019) - Grindrod, Christopher M.; Raizen, Adina L.
ABSTRACT: The goal of the current study was to investigate whether age-related changes in processing speed, as indexed by verbal fluency, modulate context use in the resolution of ambiguous idioms (e.g.,   tie the knot ). Younger and older adults completed a cross-modal priming experiment where they decided whether visual word targets were related in meaning to idiomatically or literally biased auditory sentence primes. Older adults with high verbal fluency, similar to younger adults, showed context-dependent facilitation in both biasing sentence contexts. In contrast, older adults with low verbal fluency did not show facilitation of literal meanings in literally biased sentence contexts, likely because they had difficultly inhibiting the dominant figurative meaning. These findings argue that age-related changes in context use during ambiguity resolution are restricted to older adults with reduced processing speed. The results also suggest that verbal fluency may reflect the speed in recruiting frontally-mediated selection mechanisms during ambiguity resolution.